High Magnitude Spin-Dependent Shift and Field Enhancement in BaTiO3-Based Plasmonics for Quantum Photonic Applications - Kumar, Vinit; Kumar, Ajit; Srivastava, Rupam; Sharma, Anuj K.; Prajapati, Yogendra Kumar (IEEE journal of quantum electronics, 2025)
This research investigates the integration of photonic spin-orbit interaction (SOI) with plasmonic phenomenon using Barium Titanate (BaTiO3) as the active material. A remarkable transverse spin-dependent shift (SDS) of 838~\boldsymbol {μ }m is demonstrated-approximately 28 times larger than that observed in conventional plasmonic material such as silver (Ag). The study further explores the interplay between the enhanced electric field and spin-dependent splitting under resonance conditions, revealing that the resonance angle is strongly influenced by both SDS magnitude and field enhancement. Leveraging this enhanced spin-based interaction, we demonstrate the potential for quantum-enabled optical device design, including an optical differentiator and a high-sensitivity sensor. The proposed differentiator structure exhibits a power weight of 414.96 for the co-polarized (V-V) component and 0.35 for the cross-polarized (V-H/H-V) component. Moreover, the photonic spin-based sensor architecture achieves a sensitivity enhancement of \sim~52× compared to a standard plasmonic system at a refractive index of 1.33. These findings establish BaTiO3-integrated plasmonic platforms as promising candidates for advanced spin-based photonic devices in the realm of quantum technologies.